2003
DOI: 10.1136/gut.52.7.933
|View full text |Cite
|
Sign up to set email alerts
|

13C urea breath test (UBT) in the diagnosis of Helicobacter pylori: why does it work better with acid test meals?

Abstract: Background: Acid test meals may improve the accuracy of the 13 C urea breath test (UBT). This has been attributed to changes in gastric emptying rather than to the effects of gastric pH on Helicobacter pylori urease. Aims: To determine whether enhancement of 13 CO 2 excretion in the UBT in H pylori infected volunteers by acidification of a test meal is due to a delay in gastric emptying. Methods: Urease activity in vitro was measured in intact bacteria and in bacterial homogenates. Urease activity in vivo was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
2
24
0
2
Order By: Relevance
“…Indeed, citric acid is able to sensitize the test not only by delaying gastric emptying but by a direct effect on intragastric urease activity, possibly on UreI, a proton-gated urea channel, making urea more accessible to the intrabacterial urease (499). Similar results have been found in another study where urease activity increased sixfold between pH 7 and pH 3 (431). Whether the enhanced H. pylori urease activity in vivo is strictly pH dependent or not is still a matter of debate.…”
Section: Noninvasive Testssupporting
confidence: 75%
“…Indeed, citric acid is able to sensitize the test not only by delaying gastric emptying but by a direct effect on intragastric urease activity, possibly on UreI, a proton-gated urea channel, making urea more accessible to the intrabacterial urease (499). Similar results have been found in another study where urease activity increased sixfold between pH 7 and pH 3 (431). Whether the enhanced H. pylori urease activity in vivo is strictly pH dependent or not is still a matter of debate.…”
Section: Noninvasive Testssupporting
confidence: 75%
“…Inhibition of the bacterial urease activity secondary to alkalinization of the gastric content is one of the possible explanations for the false negative UBT induced by PPIs. [20][21][22][23] Both urease activity and the transport of urea into the bacteria which is regulated by UreI-dependent specific H+-gated urea channels are pH dependent. 24 Urease activity is low at neutral pH, but as the external pH decreases to between 6.5 and 5.5 there is a 10-20-fold increase in activity which remains high through approximately pH 2.5.…”
Section: Discussionmentioning
confidence: 99%
“…In this study powdered orange juice (pH = 3.0) was taken with the capsule to increase sensitivity of the test, although citric acid as excipient of the capsule formulation may provide an acidic microenvironment. The activity of bacterial urease and the 13 CO 2 excretion were significantly higher with apple juice (pH = 3.0) or with acidified meal (pH = 3.0) than with neutral meal, and independent of gastric emptying (26) . Other authors (7,13,27) that tested 50 and or 100 mg capsule of 13 C-urea with water, showed sensitivity of 95%-100% and specificity of 97.6%-100%, suggesting that acid test meal may be omitted, lowering the cost of the exam.…”
Section: Discussionmentioning
confidence: 91%